Analisis penggunaan aplikasi Brimo dalam meningkatkan kepuasan nasabah di cabang BRI kota Palopo - mita, salmita; Afia utari; Aliya; Hidayat; Suraidah sarbia (Jurnal Ekonomi dan Bisnis Digital, 2025)
The purpose of this research is to determine how well customers accept and use the BRImo application in the city of Palopo. This study identifies the components that influence customer satisfaction with this digital banking service. The research results show that BRImo is well received, but there are several areas that need improvement, such as the system needing to be more stable and user-friendly. This study found several ways to improve the quality of BRImo services, such as optimizing features, enhancing data security, and improving customer service. As a result, BRI is expected to meet the ever-evolving expectations of customers and maintain its competitive edge in the digital banking market.